The Folklore of The Wicker Man - Jones, Leslie Ellen (Pomegranate, 2000)
The emergence of Neopaganism in the second half of the 20th century seems to be leading to a shift in the emotional associations of the Wicker Man image, inspired, I believe, by the cult popularity of The Wicker Man.